Investigating Effect of Different Parameters of the Submerged Vanes on the Lateral Intake Discharge Located in the 180 Degree Bend Using the Numerical Model - Ali Sarhadi; Ehsan Jabbari (Salehan Institute of Higher Education, 2017)
Intakes are widely used for flow diversion and its control in the open channels or rivers. During passing flow, part of the suspended sediment along with the flow enters the lateral channel and deposits in the lateral intake channel entrance, causing a change in the direction of the flow line towards the shore in front of the reservoir, which reduces the intake efficiency. Submerged vanes are small hydraulic structures that, by creating a secondary flow in their downstream, cause changes in the flow pattern and guide line to the drainage span, and the most important parameters affecting sediment input to the waterfall is the ratio of flow rate. Investigating a laboratory model has high costs and times, which in some cases cannot be justified, therefore, suitable numerical models can be proposed for such options. In this study, using Flow3D, three-dimensional numerical modeling of the flow was calibrated and verified using existing data and numerical modeling accuracy, the relative error of the numerical model was determined. In this study, all effective parameters including submerged vanes type, submerged vanes number, submerged vanes size and Froude number changes in the main channel and type of submerged vanes layout have been investigated. The results of the numerical model show that the angle of inclination of 60 degrees in the entrance intake and the chassis layout in the Froude numbers 0.21-0.33 will result in the most lateral intake discharge.